An Integrated Cooling Tunnel For Preventing The Breakage Of Chocolate Snack Bars - Md Basar, Mohd Farriz; Mohd Noh, Mohd Syahrin Amri; Yaakub, Muhamad Faizal; Amir Mohamed, Kamarul; Sam, Mustafa (Seventh Sense Research Group, 2021)
Cerealmond Confectionery SdnBhd is a manufacturer of chocolate bars in Malaysia. The manufacturer experienced significant yield loss and decreased productivity because of chocolate bars breaking on their manufacturing line. The current industry practice entails a high level of human interaction, which contributes to the occurrence of broken chocolate bars. The project's objective is to eliminate the problem of broken chocolate bars and to increase manufacturer productivity. The analysis determined that the primary issue occurred at the rotating plate, where a thermal imaging camera recorded a temperature of 28.7°C in the rotating plate area, preventing the ingredients from cooling sufficiently to harden. The solution is to maintain a low temperature in the rotating table area, which will quickly harden the chocolate bars and resolve the broken chocolate bar issue. A food-grade cooling tunnel with an acrylic container was designed for the rotating table area, resulting in a temperature of 14.7°C. As a result of the problem being resolved, the process flow was improved, resulting in a threefold increase in UPH.